Robert C. Brickell, Commissioner, The Code of Alabama, Adopted by Act of the General Assembly Approved February 28, 1887; with Such Statutes Passed at the Session of 1886-87, as are Required to Be Incorporated Therein by Act Approved February 21, 1887; and with Citations of the Decisions of the Supreme Court of the State Construing the Statutes Page 93 § 4094 - (:unkn) unknown (General Publisher, 1887)
Prohibited use of a firearm while fighting in any city, town, militia muster, or public place. Violators fined not less tha two hundred, nor more than five hundred dollars, or imprisoned in jail, or sentenced to hard labor not exceeding six months.
--
Keywords: DUELING